Social Skills Training and the Role of a Cognitive Component in Developing School Assertion in Adolescents - Yorke, Charles; McNeilly, Russell A. (Canadian Journal of Counselling and Psychotherapy, 2011)
Forty-eight Junior High School adolescents (24 males, 24 females) were screened for unassertive school behaviour and randomly assigned to one of four groups: M — modelling only, I — instructions only, M+I — modelling and instructions, or C — control. The training groups consisted of six (45-minute) non-practice sessions, followed by three (45-minute) practice meetings. Significant improvements in self-reported assertion and in assertive behaviour for school situations was found for all training groups following practice. The emphasis on face validity for what was taught, identifying topics of considerable perceived importance and immediacy, and careful attention to contextual cues (setting and person), increased the value of cognitive components in SST with unassertive adolescents and enhanced the results. For guidance counsellors, the practical value of peer mediated versus adult mediated skills training is discussed.